Is Freezing the Future? Investigating Interest of Elective Oocyte Freezing Amongst Singaporean Women - Sara Bach (Journal of Fertility Biomarkers, 2021)
A novel technological innovation called Elective Oocyte Freezing (EOF) has emerged as a solution for women who wish to preserve their fertility to delay childbearing for non-medical reasons. This technology has grown in popularity as women have undertaken a greater role in the workforce and faced the dilemma of balancing work and family. In spite of the rising trend of Singaporean women postponing childbearing to advance their careers, EOF is currently prohibited in Singapore. Many Singaporean individuals have declared this policy to be both outdated and a threat to women’s reproductive rights. However, prior to this survey, no research, to my knowledge, has analyzed Singaporean female professionals' interests in EOF, if made available. Through this quantitative, cross-sectional, 4-part survey, I conclude that if EOF was permitted, encouraged, and subsidised by the Singaporean government, Singaporean women possess a strong interest in freezing their eggs for social purposes This paper further demonstrates an existing positive relationship between 48 Singaporean female professionals’ interest in EOF prior to and following reading an information leaflet. Specifically, after being informed of the social benefits presented by EOF, participants were significantly more inclined to freeze their eggs if such practice was permitted in Singapore. This conclusion suggests that the Singaporean government should re-evaluate their position on EOF in order to facilitate childbearing dilemmas faced by the increasing number of women entering the country’s workforce each year. Additionally, as this policy is currently a subject of debate in Singapore, the implications of this research, revealing Singaporean female professionals’ interest in EOF, create a foundation for both future research and the possible evaluation of this policy. If this conclusion is corroborated with subsequent research, further evidence may substantiate my findings regarding the desires of Singaporean women and possibly result in a change of legislation.
Keywords: EOF